The Effect of Corporate Tax on Government Expenditure in Nigeria - Patrick Ologbenla (Research Horizon, 2021)
The study investigated the impact of corporate income tax on the government expenditure in Nigeria. Data on corporate income tax, value added tax, interest rate, gross domestic product, petroleum profit tax and consumer price index were collected and used as independent variable in the study while data on public expenditure were collected and used as independent variable in the estimated model. The ARDL bound test was applied and the result showed that corporate income tax have long run relationship that is significant with government expenditure. Other forms of tax such as value added tax and petroleum profit tax also have significant impact on government expenditure. The study concluded that corporate income tax should be sustained in order to ensure that government continue to fulfill her obligation of provision of social amenities that will promote the economic growth of the country.